Total Synthesis of the Proposed Structure of Paraphaeosphaeride C † - Kobayashi, Kenichi (Molecules, 2019)
Paraphaeosphaeride C is a demethoxy derivative of phaeosphaeride A and exhibits STAT3 inhibitory activity. Our previous papers reported the total synthesis of phaeosphaeride A using a diastereoselective vinyl anion aldol reaction as the key step to construct the dihydropyran ring. In this work, the first total synthesis of the proposed structure of paraphaeosphaeride C was achieved via a similar synthetic strategy. The synthetic compound was characterized through extensive nuclear magnetic resonance (NMR) analysis but the (1)H and (13)C-NMR data for this compound did not correspond to those reported in the literature for paraphaeosphaeride C.